RESISTANCE MECHANISMS OF MYCOBACTERIUM TUBERCULOSIS IN THE TUBERCULOSIS PATHOGENICITY IN HUMANS: AN OVERVIEW - Macêdo Viana, José Wellington; Pinheiro Torres, Rodolfo (Revista Interfaces: Saúde, Humanas e Tecnologia, 2022)
Tuberculosis (TB) is a chronic and serious infectious disease caused by Mycobacterium tuberculosis that mainly affects the lungs, but it is also capable of infecting other organs/tissues in the body, which triggers extra-pulmonary TB. In recent years, there has been an increase in the number of re-emerging TB cases due to resistance of M. tuberculosis to the antibiotics used to treat this disease. On top of that, there is the emergence of multidrug-resistant M. tuberculosis for which many of the antibiotics previously used have no effect. For these reasons, it was aimed to investigate the resistance mechanisms of M. tuberculosis in the TB pathogenicity in humans, considering this as a factor associated with re-emergence cases of this disease. Thus, it was carried out an integrative literature review based on articles selected in the SciElo, PubMed and Science Direct databases by using terminology in Portuguese and in English. Studies highlighted that the resistance mechanisms of M. tuberculosis consist of the emergence of mutations in target-genes naturally selected over time, the presence of efflux pumps and some lipid substances in the bacterial cell wall that provide impermeability to the antibiotics with cytoplasmic activity. Furthermore, the inappropriate use of antibiotics during the antibiotic-therapy period causes the emergence of other types of resistance. Therefore, special attention must be given to the correct use of antibiotics during the TB treatment, as well as the development of new effective drugs against multidrug-resistant bacteria strains.